2018
DOI: 10.1111/disa.12279
|View full text |Cite
|
Sign up to set email alerts
|

Digital disparities and vulnerability: mobile phone use, information behaviour, and disaster preparedness in Southeast Asia

Abstract: This paper proposes an ecological view to investigate how disparities in mobile technology use reflect vulnerabilities in communities vis-à-vis disaster preparedness. Data (n=1,603) were collected through a multi-country survey conducted equally in rural and urban areas of Indonesia, Myanmar, Philippines, and Vietnam, where mobile technology has become a dominant and ubiquitous communication and information medium. The findings show that smartphone users' routinised use of mobile technology and their risk perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 65 publications
(99 reference statements)
1
22
0
2
Order By: Relevance
“…These variables generally include individuals' perceived risk, previous experience, and knowledge regarding specific disasters of individuals to name a few . Individual perceived risks of specific disasters is a significant predictor affecting individual emergency preparedness and other risk-mitigating behaviors (Funk, Salathé, & Jansen, 2010;Lai, Chib, & Ling, 2018;Miceli, Sotgiu, & Settanni, 2008;Miceli et al, 2008;Murphy et al, 2009;Palm, Hodgson, Blanchard, & Lyons, 1990;Paton, 2008). These studies have shown that when people perceive higher risks associated with potentially disastrous events, they tend to prepare for these events more.…”
Section: Trust In Emergency Management Authorities As a Mediatormentioning
confidence: 99%
“…These variables generally include individuals' perceived risk, previous experience, and knowledge regarding specific disasters of individuals to name a few . Individual perceived risks of specific disasters is a significant predictor affecting individual emergency preparedness and other risk-mitigating behaviors (Funk, Salathé, & Jansen, 2010;Lai, Chib, & Ling, 2018;Miceli, Sotgiu, & Settanni, 2008;Miceli et al, 2008;Murphy et al, 2009;Palm, Hodgson, Blanchard, & Lyons, 1990;Paton, 2008). These studies have shown that when people perceive higher risks associated with potentially disastrous events, they tend to prepare for these events more.…”
Section: Trust In Emergency Management Authorities As a Mediatormentioning
confidence: 99%
“…Our study shows a broad availability of mobile phones in urban areas since almost all of the households have at least one mobile phone. The high availability of mobile phones and power banks potentially make mobile phones and social media good sources for risk communication (Nyunt et al 2015;Cheng et al 2016;Lai et al 2018). The percentage of smart phones users in Yangon is, however, unclear as it was not separately accessed in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Ketiga artikel mendapatkan scor 73,75 dan 78 serta dinyatakan memiliki kualitas yang baik (Tabel 1). Selain itu, dari ekstraksi data yang dilakukan, diperoleh 4 tipe intervensi dalam meningkatkan disaster preparedness, yaitu phone-based intervention, printed media intervention, peer-mentored preparedness (PM-Prep) program dan small group discussion intervention (Eisenman et al, 2009;Lai et al, 2018;Eisenman et al, 2014). Adapun karakteristik studi dari artikel yang di ekstraksi, dijabarkan pada tabel 2.…”
Section: Hasil Penelitianunclassified
“…Lingkungan pedesaan dengan komunitas yang jarang penduduk dapat menggunakan gawai sebagai salah satu media untuk mngetahui informasi terkait bencana dan tindakan kesiapsiagaan yang berguna. Penelitian lanjutan perlu dilakukan untuk mengetahui fitur dan fungsi program pada gawai yang tepat untuk masyarakat urban atau daerah pedesaan untuk menerima dan menyebar luaskan informasi terkait kebencanaan (Lai et al, 2018…”
Section: Phone-based Interventionunclassified